2011
DOI: 10.1002/app.35564
|View full text |Cite
|
Sign up to set email alerts
|

A study on the distinguishing responses of shrinkage and warpage to processing conditions in injection molding

Abstract: A challenging task in injection molding industry is to minimize shrinkage and warpage (S&W) through optimal setting of molding conditions. In determining the relationship between molding conditions and product dimension, most existing literature considered S&W as a whole entity or focused on only one of them. The intention of this study was to distinguish these two terms, and perform a thorough analysis on the effect of operative conditions on S&W during injection molding process through a combination of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Figure shows that the blend with 5 phr SAM showed the smallest domain size and narrowest size distribution. The domain size distribution of the blend was obtained by the analysis of variance method, which is one of the most widely used techniques in data analysis . Figure (b) shows the domain size distribution of the blend with SAG in amounts from 1 to 7 phr.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows that the blend with 5 phr SAM showed the smallest domain size and narrowest size distribution. The domain size distribution of the blend was obtained by the analysis of variance method, which is one of the most widely used techniques in data analysis . Figure (b) shows the domain size distribution of the blend with SAG in amounts from 1 to 7 phr.…”
Section: Resultsmentioning
confidence: 99%
“…The authors organized different sources for depicting a diagram that considered factors that affect shrinkage and warpage. Experimental evidences [10] shown that these two phenomenon were affected by different factors, even if warpage (defined as differential shrinkage) was generated by shrinkages. As consequence, a more focused structure respect to the scheme reported by Stan et al [9] was required for considering only factors that affected shrinkage.…”
Section: Structure Of Reviewmentioning
confidence: 97%
“…Studies that adopted Taguchi approach [10,50,55,63,64] or different methods [49,53,58,59,[65][66][67][68] identified this parameter as strongly critical. Shrinkage starts as soon as melted polymer fills the cavity mold and was critically influenced by holding pressure [33,69].…”
Section: Processing Parameter Influencesmentioning
confidence: 99%
“…Figure shows the size distribution of PBT/PolyASA blend with the addition of EGMA‐ g ‐SAN content. Figure was obtained from the analysis of variance technique, which is one of the widely used methods for data analysis . It is evident in Figure that the PBT/PolyASA blend with EGMA‐ g ‐SAN (3 phr) has the smallest domain size and narrowest size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 was obtained from the analysis of variance technique, which is one of the widely used methods for data analysis. 18,36 It is evident in Figure 2 that the PBT/PolyASA blend with EGMA-g-SAN (3 phr) has the smallest domain size and narrowest size distribution. The above morphological results suggest that the EGMA-g-SAN acts as a good compatibilizer in the PBT/PolyASA (70/30) blend, especially when the EGMA-g-SAN content is 3 phr.…”
Section: Resultsmentioning
confidence: 99%